Brodalumab in patients who had inadequate response to ustekinumab. (4th February 2019) - Langley, R.G.; Armstrongi, A.W.; Lebwohl, M.G.; Blauvelt, A.; Hsu, S.; Tyring, S.; Rastogi, S.; Pillai, R.; Israel, R.
Summary: Psoriasis is a chronic condition that causes red, scaly patches on the surface of the skin. Treatments may include topical (applied to the skin) creams and oral and injectable medications. Psoriasis can be caused by an autoimmune reaction in which the body's own immune system attacks healthy cells and tissues. To treat moderate‐to‐severe psoriasis, doctors sometimes use specialized medicines called antibodies, which block different parts of the autoimmune reaction that can lead to psoriasis. Although these antibody treatments can be very effective, they do not work in every patient. This study looked at data from two clinical studies of patients with moderate‐to‐severe psoriasis. In each study, patients were initially given one of two antibody treatments: ustekinumab or brodalumab. Some patients initially given ustekinumab or brodalumab did not have adequate skin clearance at week 16; these patients either started taking brodalumab (if they were initially given ustekinumab) or continued taking brodalumab (if they were initially given brodalumab) through to week 52. Patients who experienced inadequate response to their initial treatment after week 16 continued to receive their initial treatment until week 52. At week 52, patients who switched to brodalumab after an inadequate response to ustekinumab showed improvement in skin clearance. Skin clearance in patients who continued taking ustekinumab following inadequate response after week 16 was not as complete as skin clearance in those who switched to brodalumab after an inadequate response at week 16. Additionally, side effects were similar between patients who switched to brodalumab and those who remained on ustekinumab. The results of this study suggest brodalumab may be a successful treatment in patients with moderate‐to‐severe psoriasis who do not experience adequate skin clearance with other psoriasis treatments. Abstract : Linked Article: Langley et al. Br J Dermatol 2019;180 :306–314